2022
DOI: 10.1212/wnl.0000000000200145
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Semiology and Anatomo-functional Localization in Patients With Cingulate Epilepsy

Abstract: Background and Objectives:Cingulate epilepsy (CE) is a rare and challenging type of focal epilepsy, due to the polymorphic semiology of the seizures, mimicking other types of epilepsy, and the limited utility of scalp-EEG.Methods:We selected consecutive drug-resistant subjects with CE who were seizure-free after surgery, with seizure onset zone (SOZ) confirmed in the CC (cingulate cortex) by histology and/or SEEG. We analysed subjective and objective ictal manifestations using video recordings and correlated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…Because mesial temporal seizures may also manifest fearful/anxious aura and fearful facial expression, 7,29 this may reflect a continuum involving connected temporal and prefrontal components of the limbic system. Previous SEEG studies have reported fear behavior during seizures with ventromedial PFC seizure organization, [9][10][11]13 with anterior cingulate localizations, 36 and with extrafrontal seizure localizations, especially temporal or insular, often involving early propagation to frontal lobe. 6,30 Aggressive behavior during seizures was previously noted to be commoner in male patients with frontotemporal seizures and could be triggered by intrusion into the patient's peripersonal space.…”
Section: Discussionmentioning
confidence: 96%
“…Because mesial temporal seizures may also manifest fearful/anxious aura and fearful facial expression, 7,29 this may reflect a continuum involving connected temporal and prefrontal components of the limbic system. Previous SEEG studies have reported fear behavior during seizures with ventromedial PFC seizure organization, [9][10][11]13 with anterior cingulate localizations, 36 and with extrafrontal seizure localizations, especially temporal or insular, often involving early propagation to frontal lobe. 6,30 Aggressive behavior during seizures was previously noted to be commoner in male patients with frontotemporal seizures and could be triggered by intrusion into the patient's peripersonal space.…”
Section: Discussionmentioning
confidence: 96%
“…3,4,7 A rostrocaudal axis of functional organization and connectivity is increasingly recognized in the literature. 38,39 Oane et al 39 reported strong connections between the ACC and ipsilateral orbitofrontal cortex, amygdala, and contralateral ACC, whereas the aMCC has connections to the prefrontal regions, premotor and supplementary motor areas, and mesial parietal regions.…”
Section: Discussionmentioning
confidence: 99%
“…This fact cannot be explained by an alleged inability of intracerebral stimulations to generate pain, as witnessed by the fact that painful sensations are more frequently reported following the stimulation of the insular cortex, that is, the other node of the Pain Matrix. [95][96][97][98] Similarly, painful sensations are not part of the manifestations of cingulate epilepsy, 61 although they are more frequently reported in the case of insular seizures. [99][100][101][102] These facts raise a question concerning the true nature of the activation reported by neuroimaging studies on pain perception and, more specifically, regarding the hypothesis that the anterior cingulate (either pACC or pMCC) is part of the network through which pain is generated from nociception.…”
Section: From Clinical To Cognitive Neuroscience: Further Considerati...mentioning
confidence: 99%